2016
DOI: 10.1109/tcbb.2015.2415797
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Behavior of the Pancreatic <italic>β</italic>-Cell Near the Percolation Threshold: Effect of the KATPChannel On the Electrical Response

Abstract: The molecular system built with true chemical bonds or strong molecular interaction can be described using conceptual mathematical tools. Modeling of the natural generated ionic currents on the human pancreatic β-cell activity had been already studied using complicated analytical models. In our present contribution, we prove the same using our simple electrical model. The ionic currents are associated with different proteins membrane channels (K-Ca, K(v), K(ATP), Ca(v)-L) and Na/Ca Exchanger (NCX). The protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A previous study demonstrated that incretins are secreted following a meal and promote insulin secretion, thereby minimizing the fluctuation of postprandial blood glucose concentrations (8 (12). By contrast, when the glucose concentration is high, the ATP/ADP ratio is increased, thus ATP-dependent K + (K ATP ) channels close and the opening of voltage-gated Ca 2+ channels is prolonged (13). Therefore, GLP-1 causes extensive Ca 2+ influx and insulin secretion in the presence of a high concentration of glucose.…”
Section: +mentioning
confidence: 99%
“…A previous study demonstrated that incretins are secreted following a meal and promote insulin secretion, thereby minimizing the fluctuation of postprandial blood glucose concentrations (8 (12). By contrast, when the glucose concentration is high, the ATP/ADP ratio is increased, thus ATP-dependent K + (K ATP ) channels close and the opening of voltage-gated Ca 2+ channels is prolonged (13). Therefore, GLP-1 causes extensive Ca 2+ influx and insulin secretion in the presence of a high concentration of glucose.…”
Section: +mentioning
confidence: 99%